LOSSES IN GAS PIPELINES ASSOCIATED WITH THEIR LONG-TERM TERMS OPERATIONS - Martyniuk, R. Т. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
Conducted surveys of underground gas pipelines showed that their service life mainly depends on the corrosion resistance of the base metal and the welded joint of the pipes, as well as the nature of the destruction of the metal surface in places with broken insulating coating. A preliminary study of the operating conditions of underground gas pipelines made it possible to draw a conclusion about the need for complex studies of the «pipe-soil massif» system using modern methods of mechanics of underground structures and mechanics of corrosion destruction in order to prevent depressurization of gas pipelines. According to the terms of operation, 33% of main gas pipelines and 77% of main oil pipelines have been operated for more than 30 years. With the increase in the service life of pipelines with high operational parameters - diameter, pressure, length, new scientific and technical problems appear, among which, first of all, it is necessary to highlight the problem of evaluating and extending the safe service life. Almost any accidents related to the depressurization of the pipeline and the exit of the transported product entail considerable costs. A significant part of the cost goes to fines and environmental restoration (cleaning of soil, water, disposal of contaminated soil).